Tantangan Pelaksanaan Program Bantuan Pangan Non Tunai (BPNT) di Kelurahan Barengkok Kecamatan Leuwiliang Kabupaten Bogor - Aditia Saputri; Almisar Hamid (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The Non-Cash Food Assistance Program (BPNT) is assistance provided by the government to Beneficiary Families (KPM) in the form of non-cash every month. Initially, the Non-Cash Food Assistance (BPNT) program was a replacement program for the Prosperous Rice Program (Rastra) which had several problems. Presidential Regulation of the Republic of Indonesia Number 63 of 2017. This BPNT uses an electronic account mechanism, so it can only be used to buy food from traders or e-warongs that have collaborated with Himbara banks, but now BPNT assistance has changed to being in the form of money that is withdrawn at Bank link. This study aims to identify and analyze the obstacles faced in the implementation of the Non-Cash Food Assistance Program (BPNT) in Barengkok Village, Leuwiliang District, Bogor Regency. This study uses a qualitative approach with in-depth interview and observation methods. Data were collected from various sources, including beneficiaries, program implementers, and other related parties. The analysis was carried out to identify and group the main obstacles that affect the implementation of BPNT. The study identified several major obstacles in the implementation of BPNT, which were grouped into three categories: (1) Technical obstacles, including problems with infrastructure such as internet networks and EDC machines; (2) Administrative obstacles, including inaccuracies in data verification and lack of socialization about BPNT mechanisms; and (3) Socio-Economic obstacles, such as difficult access to e-warongs and low financial literacy among beneficiaries. These obstacles indicate that the implementation of BPNT in Barengkok Village faces various challenges that affect the effectiveness of the program. To improve the results and impact of BPNT, improvements need to be made in technical, administrative, and socio-economic aspects. Recommendations include improving infrastructure, improving administrative coordination, and improving education for the community.